2014
DOI: 10.1021/ef402240w
|View full text |Cite
|
Sign up to set email alerts
|

Moderate or Intense Low-Oxygen Dilution Oxy-combustion Characteristics of Light Oil and Pulverized Coal in a Pilot-Scale Furnace

Abstract: This study investigates by experiment the global characteristics of both moderate or intense low-oxygen dilution (MILD) oxy-combustion and air combustion of firing light oil and pulverized coal in a pilot-scale furnace. There are three burner configurations used, i.e., (I) central straight (primary) jet + swirl (secondary) jet, (II) central straight (primary) jet + two side symmetrical (secondary) jets, and (III) central straight (primary) jet + side asymmetrical jet. The furnace centerline temperature, specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 59 publications
4
119
1
Order By: Relevance
“…To our best knowledge, there are four kinds of definitions of the MILD combustion, i.e., (1) the definition of Wü nning and Wü nning [11], (2) the definition of Kumar et al [47], (3) the definition of Cavaliere et al [8] and (4) the definition of the present authors [45,46,48]. Wü nning and Wü nning [11] defined the MILD combustion regime using the global parameters of gas recirculation rate (K v ) and furnace temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, there are four kinds of definitions of the MILD combustion, i.e., (1) the definition of Wü nning and Wü nning [11], (2) the definition of Kumar et al [47], (3) the definition of Cavaliere et al [8] and (4) the definition of the present authors [45,46,48]. Wü nning and Wü nning [11] defined the MILD combustion regime using the global parameters of gas recirculation rate (K v ) and furnace temperature.…”
Section: Methodsmentioning
confidence: 99%
“…This definition is based on the well-stirred reactor. The definitions of the MILD combustion of burning gaseous, liquid and solid fuels are discussed in our previous study [48]. For the present study of firing gaseous fuels, the MILD combustion in experiments is defined as the flameless combustion where no visible flame front occurs at all.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, their investigation indicates that wet recirculation is more preferable in terms of NO x emission. Our recent study by Li et al 11 investigated the MILD oxy-combustion of firing both light oil and pulverized coal by experiment at a pilot-scale furnace of 300 kW and examined the effects of burner design and dilution level on the combustion appearance of liquid and solid fuels and emissions of CO and NO x . It was found that NO x reduction is more efficient under MILD oxy-combustion than the air case, while the burnout rate needs to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently reported a coal oxy-fuel combustion experimental study operated with both conventional swirl and MILD burners [35]. The results revealed that a larger NO X reduction potential could be achieved in oxy-MILD combustion as compared to the air-MILD operation, and the coal burnout was improved likewise.…”
Section: Introductionmentioning
confidence: 99%
“…The applications also indicate a higher thermal efficiency under oxy-MILD combustion than conventional oxy-fuel combustion or air-MILD combustion. As for coal oxy-MILD combustion, the corresponding studies are quite sparse, however, the latest literatures still can be found elsewhere [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%